2014
DOI: 10.1177/1087054714558874
|View full text |Cite
|
Sign up to set email alerts
|

Bullying Victimization and Perpetration and Their Correlates in Adolescents Clinically Diagnosed With ADHD

Abstract: A high proportion of adolescents with ADHD are involved in bullying. Multiple factors are associated with bullying involvement in adolescents with ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 57 publications
3
44
2
3
Order By: Relevance
“…Previous studies of peer victimization in youth with ADHD have reported prevalence rates ranging from 19% to 43% [9,11,12]. In the current study, 57% of participants reported experiencing at least one victimization behavior at a rate of at least once per week.…”
Section: Discussionmentioning
confidence: 44%
See 3 more Smart Citations
“…Previous studies of peer victimization in youth with ADHD have reported prevalence rates ranging from 19% to 43% [9,11,12]. In the current study, 57% of participants reported experiencing at least one victimization behavior at a rate of at least once per week.…”
Section: Discussionmentioning
confidence: 44%
“…In line with research linking ADHD to higher rates of peer rejection [1], studies have found that youth with ADHD experience higher rates of victimization than their peers [9,10]. For instance, Twyman et al [11] found that 29% of youth with ADHD (ages 8–17 years) reported experiencing elevated rates of peer victimization, in contrast to 9% of youth without a psychiatric diagnosis.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…[3] Klini¤e gelen olgumuzda oldu¤u gibi DEHB olan çocuk veya ergenlerde, özellikle de davranım bozuklu¤u elik etmiyorsa, arkadaları tarafından u¤radıkları zorbalık davranıları kendileri ya da ebeveynleri tarafından dile getirilse de bu davranılar DEHB belirtileri olarak ele alınabilmektedir. Nitekim Chou ve ark.nın [9] 287 DEHB olan ergen ile yaptıkları çalımada; olguların %14.6'sının akran zorbalı¤ı yaptı¤ı, %5.6'sının da kurban oldu¤u, %8.4'ünün hem kurban hem de uygulayan oldu¤u bildirilmitir. Dikkat eksikli¤i hiperaktivite bozuklu¤u olan çocukların %13'ünün akran zorbalı¤ı kurbanı oldu¤u özellikle vurgulanmalıdır.…”
Section: Tartimaunclassified